Perinatal exposure to glyphosate-based herbicide alters the thyrotrophic axis and causes thyroid hormone homeostasis imbalance in male rats - de Souza, Janaina Sena [UNIFESP] (2017)
Glyphosate-based herbicides (GBHs) are widely used in agriculture. Recently, several animal and epidemiological studies have been conducted to understand the effects of these chemicals as an endocrine disruptor for the gonadal system. The aim of the present study was to determine whether GBHs could also disrupt the hypothalamic-pituitary-thyroid (HPT) axis. Female pregnant Wistar rats were exposed to a solution containing GBH Roundupo (R) Transorb (Monsanto). The animals were divided into three groups (control, 5 mg/kg/day or 50 mg/kg/day) and exposed from gestation day 18 (GD18) to post-natal day 5 (PND5). Male offspring were euthanized at PND 90, and blood and tissues samples from the hypothalamus, pituitary, liver and heart were collected for hormonal evaluation (TSH-Thyroid stimulating hormone, T3-triiodothyronine and T4-thyroxine), metabolomic and mRNA analyses of genes related to thyroid hormone metabolism and function. The hormonal profiles showed decreased concentrations of TSH in the exposed groups, with no variation in the levels of the thyroid hormones (THs) T3 and T4 between the groups. Hypothalamus gene expression analysis of the exposed groups revealed a reduction in the expression of genes encoding deiodinases 2 (Dio2) and 3 (Dio3) and TH transporters Slco1c1 (former Oatp1c1) and Slc16a2 (former Mct8). In the pituitary, Dio2, thyroid hormone receptor genes (Thra1 and Thrb1), and Slc16a2 showed higher expression levels in the exposed groups than in the control group. Interestingly, Tshb gene expression did not show any difference in expression profile between the control and exposed groups. Liver Thra1 and Thrb1 showed increased mRNA expression in both GBH-exposed groups, and in the heart, Dio2, Mb, Myh6 (former Mhca) and Slc2a4 (former Glut4) showed higher mRNA expression in the exposed groups. Additionally, correlation analysis between gene expression and metabolomic data showed similar alterations as detected in hypothyroid rats. Perinatal exposure to GBH in male rats modified the HPT set point, with lower levels of TSH likely reflecting post-translational events. Several genes regulated by TH or involved in TH metabolism and transport presented varying degrees of gene expression alteration that were probably programmed during intrauterine exposure to GBHs and reflects in peripheral metabolism. In conclusion, the role of GBH exposure in HPT axis disruption should be considered in populations exposed to this herbicide. (C) 2016 Elsevier Ireland Ltd. All rights reserved.